2017
DOI: 10.1051/0004-6361/201731170
|View full text |Cite
|
Sign up to set email alerts
|

First detection of methanol towards a post-AGB object, HD 101584

Abstract: The circumstellar environments of objects on the asymptotic giant branch and beyond are rich in molecular species. Nevertheless, methanol has never been detected in such an object, and is therefore often taken as a clear signpost for a young stellar object. However, we report the first detection of CH 3 OH in a post-AGB object, HD 101584, using ALMA. Its emission, together with emissions from CO, SiO, SO, CS, and H 2 CO, comes from two extreme velocity spots on either side of the object where a high-velocity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…In the protoplanetary disk around DG Tau, a T Tauri star, disk-height-averaged column densities of H 2 CO and CH 3 OH were estimated at ∼0.3−4 × 10 14 cm −2 and <0.04−0.7 × 10 14 cm −2 , respectively, with a CH 3 OH/H 2 CO abundance ratio <1 and a H 2 CO ring located beyond the CO snow line (Podio et al 2019). In the circumstellar envelope of the post-asymptotic giant branch (AGB) object HD 101584 (Olofsson et al 2017), H 2 CO, H 13 2 CO, and CH 3 OH were also observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the protoplanetary disk around DG Tau, a T Tauri star, disk-height-averaged column densities of H 2 CO and CH 3 OH were estimated at ∼0.3−4 × 10 14 cm −2 and <0.04−0.7 × 10 14 cm −2 , respectively, with a CH 3 OH/H 2 CO abundance ratio <1 and a H 2 CO ring located beyond the CO snow line (Podio et al 2019). In the circumstellar envelope of the post-asymptotic giant branch (AGB) object HD 101584 (Olofsson et al 2017), H 2 CO, H 13 2 CO, and CH 3 OH were also observed.…”
Section: Introductionmentioning
confidence: 99%
“…This implies a fractional abundance of methanol of the order of X(CH 3 OH)≈10 −8 -10 −7 . This value, while it is expected to have large errorbars, is intermediate to the methanol fractional abundance found in the post-AGB object HD 101584 (~3×10 −6 , Olofsson et al 2017) and in the yellow hypergiant IRC+10420 (~7×10 −8 , Quintana-Lacaci et al 2016).…”
Section: Resultsmentioning
confidence: 58%
“…The detection of CH 3 OH in evolved stars has remained elusive until very recently. Indeed, OH 231.8 is the first CSE of an AGB star in which gas-phase methanol has been identified, after the recent discovery of this molecule with ALMA in the post-AGB object HD 101584 (Olofsson et al 2017). Only one year before, methanol was detected in the yellow hypergiant IRC+10420 (Quintana-Lacaci et al 2016), although this is a different class of object descending from a much more massive star (~50 M ⊙ ) than QX Pup and HD 101584.…”
Section: Resultsmentioning
confidence: 99%
“…Another infrared interferometric imaging campaign was performed on HD101584 that has been extensively studied with the Atacama Large Millimeter/submillimeter Array (ALMA). [33][34][35] These observations revealed a bipolar environment as traced by the CO gas (see Fig. 2).…”
Section: Revealing a Complex Environment: Imaging Hd101584mentioning
confidence: 72%